2000
DOI: 10.1046/j.1462-2920.2000.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironments and distribution of nitrifying bacteria in a membrane‐bound biofilm

Abstract: The distribution of nitrifying bacteria of the genera Nitrosomonas, Nitrosospira, Nitrobacter and Nitrospira was investigated in a membrane-bound biofilm system with opposed supply of oxygen and ammonium. Gradients of oxygen, pH, nitrite and nitrate were determined by means of microsensors while the nitrifying populations along these gradients were identified and quantified using fluorescence in situ hybridization (FISH) in combination with confocal laser scanning microscopy. The oxic part of the biofilm which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
168
5
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(193 citation statements)
references
References 36 publications
18
168
5
2
Order By: Relevance
“…In contrast to the aerobic incubation experiments, no uptake of organic or inorganic carbon sources by Nitrospira-like bacteria was observed in the absence of oxygen. However, combined FISH and microsensor measurements revealed that high numbers of Nitrospira-like bacterial cells can persist in biofilm zones with low oxygen pressure (17,36,41). The ability to switch from aerobic respiration to an anaerobic metabolism should be advantageous in such habitats.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the aerobic incubation experiments, no uptake of organic or inorganic carbon sources by Nitrospira-like bacteria was observed in the absence of oxygen. However, combined FISH and microsensor measurements revealed that high numbers of Nitrospira-like bacterial cells can persist in biofilm zones with low oxygen pressure (17,36,41). The ability to switch from aerobic respiration to an anaerobic metabolism should be advantageous in such habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial segregation along vertical gradients is a well-known feature of microbial communities in aquatic biofilms, microbial mats, and endolithic communities (Schramm et al, 2000;Paerl et al, 2000). Similar to the Winogradsky column, these microbial stratifications are driven by the distribution of electron acceptors and donors.…”
Section: Microbial Community Stratification Within Biocrustsmentioning
confidence: 99%
“…This in time separated growth and installation of AOB and NOB results in an initial Rittman et al (1999) nitrite peak. As AOB catalyse the first reaction of the two-step nitrification, making the NOB wait for their substrate, and because the AOB have a higher yield (Table 3), dominance of AOB and accumulation of nitrite is to be expected for the start-up phase of a nitrifying bioreactor (Schramm et al 2000). It was demonstrated (Bovendeur 1989) that in developing biofilms nitratation capacity develops with some delay after the development of nitritation, leading to initial higher nitrite concentrations.…”
Section: Accumulation Of Nitritementioning
confidence: 99%